To Build a Model for the Determination of Factors that Result in the Success of the Organized Retail Sector in India and Analyzing its Relative Importance (With Reference to Fast Food Chains and Grocery and Vegetable Outlets) - Malik, Ruchi (Indian Journal of Marketing, 2012)
Organized retailing has definitely made headway in the society. In order to appeal to all classes of the society, retail stores would have to identify with customer tastes and preferences. The present study deals with the identification of the factors affecting the success of organized retail sector and analyzing their importance. These factors are broadly classified as micro and macro-level factors. The latter includes all the environmental factors that are largely uncontrollable. The micro level factors provide an individualistic point of view, i.e. it includes parameters that may affect customer’s perception and purchase behaviour. In other words, it includes those factors that ultimately lead to demand creation. On the basis of literature studied, lists of factors (though the list might not be exhaustive) have been identified and their impact across two different segments of retail (food chains, grocery and vegetables outlets) has been analyzed. It was found from the study, that though there are multitudinous opportunities that are untapped by the retailers, they can be successful by paying more attention towards their customer needs and desires. Today’s customer is not just influenced by price and quality. There are many other factors that drive him towards the store. The retailers have to pay attention to these factors i.e. formulating the right marketing strategies in order to tap more customer base and become successful in this competitive environment.